The Relationship Between Service Quality and Patient Satisfaction Following Caesarean Section Among JKN-PBI Patients at Grandmed Hospital Lubuk Pakam - Ulina Purba, Sri; Karnirius Harefa; Ramadani Sitepu (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
This study aims to analyze the relationship between service quality and patient satisfaction among post–Sectio Caesarea (SC) patients who are beneficiaries of the National Health Insurance – Contribution Assistance Recipients (JKN-PBI) at Grandmed Hospital Lubuk Pakam in 2024. Patient satisfaction is one of the key indicators in evaluating hospital service quality. Good service quality is expected to improve patient satisfaction, particularly among JKN-PBI participants who often face administrative and service-related challenges. This research employed a quantitative analytic survey with a cross-sectional approach. The population consisted of all post-SC patients using JKN-PBI at Grandmed Hospital Lubuk Pakam. A total of 52 respondents were selected using the accidental sampling technique. Data were collected through questionnaires and analyzed using the Chi-Square test. The results showed a significant relationship between several dimensions of service quality and patient satisfaction, namely: 1) Speed of service (p = 0.049), 2) Courtesy and friendliness of staff (p = 0.021), and 3) Supporting service facilities (p = 0.023). Thus, the better the quality of hospital services, particularly in terms of responsiveness, courtesy, friendliness, and supporting facilities, the higher the level of patient satisfaction.